Hospital-Wide SARS-CoV-2 Antibody Screening in 3056 Staff in a Tertiary Center in Belgium - Steensels, Deborah (JAMA, 2020)
This study characterizes the prevalence of antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among hospital staff of a Belgian tertiary care center tested over 1 week in April 2020, and risk factors for seropositivity.